2022
DOI: 10.1088/2631-7990/ac5e13
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular and surface forces in atomic-scale manufacturing

Abstract: Atomic and close-to-atomic scale manufacturing (ACSM) aims to provide techniques for manufacturing in various fields, such as circuit manufacturing, high energy physics equipment, and medical devices and materials. The realization of atomic scale material manipulation depending on the theoretical system of classical mechanics faces great challenges. Understanding and using intermolecular and surface forces are the basis for better designing of atomic and close-to-atomic scale manufacturing. Transformation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 125 publications
0
9
0
Order By: Relevance
“…Most significantly, so many focal points in a limited space can greatly improve the efficiency of space utilization, which is critical for high-cost and highly difficult micro-nano fabrication processes. Such a multifocal metalens can be fabricated using electron beam lithography (EBL), atomic layer deposition (ALD) [ 14 , 53 , 54 ], and ion beam polishing (IBP) [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most significantly, so many focal points in a limited space can greatly improve the efficiency of space utilization, which is critical for high-cost and highly difficult micro-nano fabrication processes. Such a multifocal metalens can be fabricated using electron beam lithography (EBL), atomic layer deposition (ALD) [ 14 , 53 , 54 ], and ion beam polishing (IBP) [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the limitations of those existing fabrication techniques make it difficult to fabricate three-dimensional (3D) metamaterials [ 9 , 10 ]. Therefore, the two-dimensional (2D) metamaterials, metasurfaces, have been rapidly developed and applied owing to their relatively easy fabrication methods and technologies [ 11 , 12 , 13 , 14 , 15 , 16 ]. Moreover, metasurfaces can control the amplitude [ 17 , 18 , 19 , 20 ], phase [ 21 , 22 , 23 , 24 ], and polarization [ 25 , 26 , 27 , 28 ] of electromagnetic waves, leading to a fact that various applications based on their unique properties have been developed, such as metalens focusing [ 29 , 30 , 31 ], holographic imaging [ 32 ], vortex light modulation [ 33 ], and abnormal deflectors [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…This section will focus on the anisotropy effect on the damage evolution induced by cleavage fracture and slip deformation. Figure 9(a) is the schematic diagram of the cleavage fracture of MgF 2 single crystals, where the resolved tensile stress σ k is the driving stress acting on the cleavage plane, as given in equation (10),…”
Section: Anisotropy Effect On Damage Evolution Induced By Crystal-pla...mentioning
confidence: 99%
“…Scratch tests can accurately control the scratch speed and normal load at nano-and micro-scales, and can accurately obtain the penetration depth and scratch force during the scratch process. Therefore, it is widely used in studying the damage evolution and material removal of hard and brittle materials at nano-and micro-scales [10][11][12]. Li et al [13] analyzed the damage evolution and deformation mechanism of GaN crystals using nanoscratch tests, and they found that there were polycrystalline nanocrystals, phase and amorphous transformations and close-to-atomic-scale damages in the plastic deformation zone of the scratched subsurface.…”
Section: Introductionmentioning
confidence: 99%
“…Under extreme heavy-duty cutting conditions, severe tool wear is induced by impact damage and interface friction [26]. Moreover, the friction issues in precision and ultra-precision manufacturing are especially pronounced because of the size effect [40,56]. As the depth of cut approaches the tool edge radius, the cutting-dominant pattern gradually transforms into cutting shear, ploughing, and adhesive friction [57,58].…”
Section: Diverse Cutting Conditionsmentioning
confidence: 99%